Hybrid and active learning methodologies with the use of information and communication digital teaching technologies: the resumption of a conceptual foundation and perspectives for higher education (Research, Society and Development, 2022)
This article addresses aspects of the incorporation of active learning methodologies and the adoption of blended learning in the context of Higher Education with the use of Digital Information and Communication Technologies (TDIC). The article is part of a thesis research of the Doctorate in Education at the University of Uberaba (UNIUBE), in progress, entitled "Teaching-learning processes and implementation of active education methodologies with the use of Digital Information and Communication Technologies among students". years 2015 and 2021”. The objective was to build a conceptual foundation on blended teaching and active learning methodologies with the use of TDIC in Higher Education. Therefore, a literature review was carried out, followed by the reading of works by authors who were not included in the first phase of the bibliographic analysis carried out during the preparation of the thesis. From the inclusion of new studies, it was possible to expand the conceptual basis of the doctoral thesis and glimpse perspectives for the adoption of innovative pedagogical practices in Higher Education.